Pa' Umor Salt - Short Video - Jussem, S.W; Rafee, Y.M; Siri, H.; Awang Arshad, A.H; Abol Hassan, M.Z (Youtube, 2020)
This short video with a duration of 3 minutes and 47 seconds is a summary of the salt production process in the Kelabit highlands. The filming was done in Pa ’Umor, Bario and funded under the Dayak Chair grant (F03 / DRC / 1650/2018). This video has won third place in the Old Kuching Smart Heritage (OKSHe) video competition and the video can be viewed via https://www.youtube.com/watch?v=AKbRi16qSuc